Disjunction and extraction of maxillary first premolars in malocclusion Class II division 1 mesofacial patient - Gallardo Moreno, Wenceslao (Revista Universidad de Guayaquil, 2013)
The patient was a healthy 9 year old boy with malposition of the teeth in mixed dentition, in the facial profile analysis, an apparent increase in the lower third of the face is noticed, jaw is slightly retrognatic. .Class II Div 1 malocclusion, Incomplete eruption of dental piece 11, piece 12 has not erupted. (Tooth Identification , FDI system), showing slight giroversion of lower central incisors, overjet increased 5.5 mm, crossbite of upper right supporting area (primary pieces: canine, first and second molar). Upper midline was coincident with facial midline, teeth midline maxillary and mandibular aren’t coincident in centric occlusion or centric relation. , their mandibular dental midline is shifted 1½ mm to the right of the patient in centric occlusion and centric relation. He was treated with orthotics (maxillary disjunction) and orthodontics through the extraction of maxillary first premolars, upper incisor retrusion, leveling and alignment of the upper and lower dental arches. The total time of active treatment in the different phases was 5 years 10 months. Pre and Post treatment records are shown. Overjet, overbite and Spee curve are evident in the standard, and excellent alignment and symmetry in the dental arches. At the end of the case Class II molar and Class I canine relationship Is noticed. We obtained a very good facial aesthetics, no clinical discrepancy between OC and RC. The TMJ was free of symptoms.